2021
DOI: 10.3390/su13179661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytoremediated Port Sediment as an Agricultural Medium for Pomegranate Cultivation: Mobility of Contaminants in the Plant

Abstract: Although the dredging of ports is a necessary management activity, it generates immense quantities of sediments, that are defined by the European Union as residues. On the other hand, the relevant peat demand for plant cultivation compromises its availability worldwide. In this context, the present work wanted to find an alternative substrate in order to replace and/or reduce the use of peat in agriculture, through the study of the suitability, concerning the exchange of substrate–plant–water pollutants, of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A positive effect of the TS was evidenced on calla lily, notoriously known as a water demanding species. In fact, due to its clayey silt composition, the sediment can increase water retention capacity when added to traditional soilless growing media, although the effect appears to depend primarily on the amount of sediment added to the medium (MartínezNicolás et al, 2021). In our study, both tested sedimentbased mixtures allowed a copious blooming, while a 30% water reduction determined a highly significant decrease in flower production.…”
Section: Discussionmentioning
confidence: 57%
“…A positive effect of the TS was evidenced on calla lily, notoriously known as a water demanding species. In fact, due to its clayey silt composition, the sediment can increase water retention capacity when added to traditional soilless growing media, although the effect appears to depend primarily on the amount of sediment added to the medium (MartínezNicolás et al, 2021). In our study, both tested sedimentbased mixtures allowed a copious blooming, while a 30% water reduction determined a highly significant decrease in flower production.…”
Section: Discussionmentioning
confidence: 57%
“…The area presented high insolation, with approximately 3000 h of sunshine per year. The highest sunshine percentage was registered during the summer months (more than 352 h in July) and the lowest in December and January [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tozzi et al [ 159 ] applied remediated marine sediment as a growing medium for lettuce production; results showed that the plants were rich in minerals, organic acids, and antioxidant, but no symptoms of phytotoxicity were found. Martínez-Nicolás et al [ 160 ] used port sediment as an agricultural medium for pomegranate cultivation, confirming that transfer of pollutants is limited and dredged sediments could be applied for agricultural activities. However, their applications were restricted due to the common pollutants (heavy metals and polycyclic aromatic hydrocarbons).…”
Section: Resource Utilizationmentioning
confidence: 98%